PEMANFAATAN TEPUNG SUKUN DALAM PEMBUATAN FRENCH BREAD: PEMANFAATAN TEPUNG SUKUN DALAM PEMBUATAN FRENCH BREAD - Atmojo, Heri; Astriana Dewi, Camilah (Akademi Pariwisata NHI Bandung, 2024)
ABSTRACTThe study aims to determine the difference in the taste of French Bread using breadfruit flour with French Bread comparison, nutritional value and production costs. The type of research used is experimental with data collection techniques of observation, questionnaires, literature study and assessment of professional and non-professional panellists through organoleptic tests and hedonic tests. The measurement scale uses Likert, with data analysis techniques through interviews, field notes, and documentation. The conclusions and suggestions are, 1. The experimental French bread has not significantly competed with the comparison French bread as a delicious and nutritious new innovation. Except for people with celiac or gluten allergy.2. The nutritional content of the two products, the amount of kandugan owned is not much different, french bread from breadfruit flour is very suitable in making gluten free ingredients for people who have celiac disease. 3. The cost difference is quite significant. Experimental French Bread is healthier, nutritious, rich in benefits, worth commercialising. The flavour aspect with breadfruit flour French bread i does not meet the standard, the experimental French bread is more different from the texture, aroma and taste 2. The cost of production of experimental French bread is quite significant, but on the grounds of consumer health there is a choice, 3. The nutritional value of experimental French bread is less than comparative French bread because the ingredients are not comparable to comparative Keywords: French Bread, Breadfruit flour, Wheat flour, Taste, Nutrition & Cost